Investigating the influence of a wine yeast consortium on population dynamics, alcoholic and malolactic fermentation - Janse van Rensburg, Philippe Jacques (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.